2010
DOI: 10.1038/nrg2918
|View full text |Cite
|
Sign up to set email alerts
|

Network medicine: a network-based approach to human disease

Abstract: Given the functional interdependencies between the molecular components in a human cell, a disease is rarely a consequence of an abnormality in a single gene, but reflects the perturbations of the complex intracellular network. The emerging tools of network medicine offer a platform to explore systematically not only the molecular complexity of a particular disease, leading to the identification of disease modules and pathways, but also the molecular relationships between apparently distinct (patho)phenotypes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
3,716
2
68

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 4,173 publications
(3,828 citation statements)
references
References 135 publications
42
3,716
2
68
Order By: Relevance
“…18,19 This seems intuitive since organisms demonstrate modularity and conservation of biology across evolution. 20,21 One such approach, weighted gene co-expression network analysis (WGCNA), uses the property of coexpression to organize genes into gene networks or modules. 22 Here we develop a co-expression framework called the 'toxicogenomic module associations with pathogenesis' (the TXG-MAP) and integrate it with standard pathology evaluation to characterize mechanisms of drug-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 This seems intuitive since organisms demonstrate modularity and conservation of biology across evolution. 20,21 One such approach, weighted gene co-expression network analysis (WGCNA), uses the property of coexpression to organize genes into gene networks or modules. 22 Here we develop a co-expression framework called the 'toxicogenomic module associations with pathogenesis' (the TXG-MAP) and integrate it with standard pathology evaluation to characterize mechanisms of drug-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular biologists have come to recognize the importance of this, as witnessed by discussions of 'gene regulatory networks' and the recent terminological shifts from 'metabolic pathway' to 'metabolic network' and from 'signaling pathway' to 'signaling network.' Many researchers emphasize that since there is 'cross-talk' between what deemed to be separate pathways, the larger network needs to be studied (Barabási et al, 2011;Fraser & Germain, 2009;Jørgensen & Linding, 2010;Layek et al, 2011;Wing et al, 2011). Furthermore, the organization of causal interactions is not unidirectional and acyclic, but mechanisms have feedback loops (Bechtel, 2011).…”
Section: Mechanismsmentioning
confidence: 99%
“…On the other hand, it also calls for reconsideration of the dominant health policy thinking, which is too deterministic and not equipped to take into account the interconnected nature of many diseases as well as their social determinants [4] Furthermore, looking at specific networks as determinants of health or disease allows us to reconsider the relationship between genes and environment. For instance, by analysing data on genetic structure in a large scale population provided by the National Longitudinal Study of Adolescent Health and the Framingham Heart Study, Fowler et al [23] showed that the genetic structure may be less determined by reproduction constraints (e.g.…”
Section: The Network Medicine Approach To Public Health Policymentioning
confidence: 99%